Kebijakan Pemberlakuan Politik Demokrasi dan Pengaruhnya Terhadap Kesejahteraan Sosial - Moh. Zaini (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
Democracy can not be used as the major target factor, because the run of the democratic system depends on its bureaucrat, system implementation and administration process. Although the democratic system has been used by almost every country in the world, it does not automatically guarantee people’s prosperity. Abraham Lincoln’s concept of democracy; from the people, by the people, for the people, is actually a ‘target between’ a combination of countries’ ideology and the interests of the political map oriented to the interests of public welfare.